Hubungan Morfologi Ventrikel Kiri Orang Terlatih dengan Respons Hipoksia di Ruang Udara Bertekanan Rendah - Adhantoro Rahadyan; Andang H Joesoef; Dolly R.D Kaunang (The Indonesian Heart Association, 2008)
Background. The higher the altitude, the higher the risk to hypoxia exposure. Good fitness status of airplane pilot has been thought of great importance to encounter hypoxic risk. Meanwhile, intensive endurance training results in increase of left ventricular mass and change of cardiac function due to down regulation of beta adrenergic receptor. It is not clear whether the difference in myocardial morphology due to endurance training will cause difference tolerance in hypoxia responses.Objectives. To compare hypoxia response of trained and untrained men and to investigate association of left ventricle morphology and hypoxia responses.Methods. This is a cross-sectional study involving 128 trained and 25 untrained men. They underwent medical examination in Saryanto Institute of Aerospace Medicine, Jakarta. Echocardiography and treadmill test ex-amination were performed. The time of useful consciousness (TUC) was measured using 25,000 feet hypobaric stimulation chamber.Results. Six subjects were excluded due to incomplete data. The mean age of trained men was 22 ± 1.0 years. TUC of trained (n=122) and untrained (n=25) men were 232 ± 64 sec and 260 ± 51 sec, respectively (p=0.01). To evaluate for association between echocardiographic parametric of ventricle morphology and TUC, all subjects were divided into TUC < 4 min and TUC = 4 min. Parameters related to TUC are LVEDD and LVMI. TUC < 4 min related to larger LVEDD and LVMI. Conclusion. Trained men had shorter TUC compared to untrained men. Shorter TUC related to larger LVEDD and LVMI.